Principal Leadership Management - Henny N. Tambingon; Joulanda A.M. Rawis; Mozes M. Wullur; Jehezkiel Panjaitan; Mendy Juniaty Hatibie; Maximillian Christian Oley (Return : Study of Management, Economic and Bussines, 2024)
This research focuses on the leadership management of the principal of SMP Negeri 1 Sonder. The formulation of the problem in this study is How to Understand School Principals about Leadership Management in Country 1 Sonder. How school principals in Negeri 1 Sonder implement leadership management and how school principals strive to improve leadership management. This study uses a qualitative research method that is qualitative descriptive. Observations, documents and interviews are used as data collection techniques. Based on the formulation of the problem and the results of the field study, several conclusions were drawn, including: The leader, namely the principal, understands that leadership management is a very important thing that helps him in organizing, carrying out and assuming responsibilities as a leader or principal. The principal carries out or implements his leadership by fulfilling his leadership duties even though it has not been maximized and fostering good relationships with teachers, students, and parents. The principal also strives to improve leadership management at SMP Negeri 1 Sonder, so that the principal strives for educational conditions to run well by dividing tasks, creating an organizational structure, controlling all tasks given to teachers, fostering good relationships and communication between the school, the government, parents and the community, as well as approaching teachers and students and trying to be leaders for the progress of the school.